The Role of Digital Transformation on Marketing Performance of Bird Cages in Ajibarang with Digital Marketing as a Mediation Variable (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in increasing innovation and creativity so that they can improve economy. MSMEs can increase the community's economy by providing employment, and producing products or services needed by the community. More than 300 MSME bird cage craftsmen in the Ajibarang, who are recorded or who have not been recorded, are able to absorb labor so that they can reduce the unemployment rate. In its journey, MSMEs bird cage craftsmen in Ajibarang facing many problems, one of which was not maximizing technology in marketing. They are still using a personal selling strategy. This study aims to examine the effect of digital marketing on marketing performance. This study also eximing digital transformation is able to mediate digital marketing and marketing performance. The sample used in this study was 97 respondents with a purposive sampling technique. Based on the results of research conducted using Smart PLS, it shows that digital transformation has a positive effect on digital marketing and marketing performance. Digital marketing is able to mediate digital transformation variable and marketing performance variable. The digital transformation in Ajibarang bird cage craftsmen MSMEs, will increase their digital business marketing capabilities and will increasing marketing performance. Increasing digital transformation of the Ajibarang bird cage craftsmen MSMEs will lead to increased productivity, innovation, and creativity of MSME in facing business competition. The implication of this research is that the results of the research are able to become the resources for MSME Ajibarang bird cages in determining the right strategy to improve their marketing performance.